2003
DOI: 10.1520/jfs2002209
|View full text |Cite
|
Sign up to set email alerts
|

Testing for GHB in Hair by GC/MS/MS after a Single Exposure. Application to Document Sexual Assault

Abstract: Although considered as a new drug of abuse, gamma-hydroxybutyrate, or GHB, has been used clinically since the 1960s as an intravenous anesthetic. It was also investigated for treatment of insomnia, of alcohol and opiate withdrawal syndrome, and in cerebrovascular disorders. GHB is a substance naturally present within mammalian species. Properties of neurotransmitter or neuromodulator are generally given to this substance (1,2). Doses of 10 mg/kg cause amnesia; 20 to 30 mg/kg cause sleep; and doses of 50 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 20 publications
6
72
0
4
Order By: Relevance
“…The very low concentrations detected in the 2nd and 3rd cm from the scalp well represent the physiological GHB level of the subject, in agreement with the normal level observed in human hair (≤2 ng/mg). The quite higher concentration observed in the first segment was reasonably due to the endogenous GHB incorporation through sweat at the root level, as reported in the literature [11,14].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The very low concentrations detected in the 2nd and 3rd cm from the scalp well represent the physiological GHB level of the subject, in agreement with the normal level observed in human hair (≤2 ng/mg). The quite higher concentration observed in the first segment was reasonably due to the endogenous GHB incorporation through sweat at the root level, as reported in the literature [11,14].…”
Section: Discussionsupporting
confidence: 83%
“…We obtained an estimated concentration of 0.28 ng/mg with GC-MS, and 0.27 with LC-MS/MS, in the low end of the range reported in the literature [11][12][13][14][15]; we subsequently used the calibration curves obtained with that specific matrix to quantify QCs and samples, and corrected the amounts of found GHB by adding the value of the "blank." Obviously, when using the standard addition method, the GHB content of the blank must be recalculated in case calibration curves are prepared with fresh hair.…”
Section: Validation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In a nearly 4-year-long study in the English town of Merseyside, 42 children were reported with methadone intoxication. 5 Methodone overdose in children in the US is significant as well.…”
Section: Discussion Clinical Presentationsmentioning
confidence: 99%
“…Celle-ci présente l'avantage de pouvoir mettre en évi-dence le GHB plusieurs semaines après les faits. Les cheveux peuvent être utilisés comme un calendrier historique et permettent de détecter une exposition unique au GHB (3,4). Il n'y a pas de publication à ce jour sur la détection du GHB dans les poils pubiens.…”
Section: Introductionunclassified